Pengaruh Terapi Oksigen Hiperbarik sebagai Adjuvan Radioterapi dan Kemoterapi terhadap Sel Kanker - Windu Asmara Putra Arya Arya; Djati Widodo Edi Pratiknya; Nabil Bahasuan (Universitas Hang Tuah, 2021)
Background : Cancer is non-infectious disease that become world”s burden today. In order to support the main treatment for cancer, hyperbaric oxygen therapy can be an option to be adjuvant therapy. Goal of this research is to know the influence of hyperbaric oxygen therapy as an adjuvant to radiotherapy and chemotherapy at cancer cell. Method : This research use literature review as a method. Journal that used in this research is international journal that indexed in scimago or national journal that indexed in sinta that published from 2016 up to 2021. This research is held from April 2021 – September 2021. Research has been done in Fakultas Kedokteran Universitas Hang Tuah Surabaya. Results : In this research, 11 studies has been collected where 10 among them stated that hyperbaric oxygen therapy give an influence toward radiotherapy and chemotherapy at cancer cell, while 1 study show there are no influence at all toward radiotherapy and chemotherapy. There are limitations in this research where studies which reviewed have different instruments, design, and therapeutic dose, thus make this research difficult to conclude. Conclusion : 10 from 11 studies show hyperbaric oxygen therapy vary in effect to radiotherapy and chemotherapy in cancer cell like effication, sensitivity, work, toxicity effect, and inhibition effect improvement, also improvement of survival rate at cancerous patient, while 1 study show hyperbaric oxygen therapy has no effect toward radiotherapy and chemotherapy.